The Female Accomplice: Rape, Liberalism, and the Eighteenth-Century English Novel - (:unkn) unknown (My University, 2016)
Previous scholarship on rape narratives within the emerging eighteenth-century novel focuses on a dichotomous construction of the female agent struggling against the male rapist and against a biased patriarchal society. However, my project expands this gendered model by evaluating how the presence of colluding female accomplices complicate understandings of female agency and patriarchal violence. I argue that depictions of femes soles as treacherous and mercenary liberal subjects, who embody the corruption of the market, play a vital part in domesticating single women of the developing middle class. I analyze the ways in which female accomplices to rape represent a sizeable population of vilified, contracted, women workers or economically independent femes soles, who operate independently of the marriage contract and threaten marriageable women’s consensual agency in an era that began to ideologically champion women’s consensual rights to sex and marriage. By extension, I argue these felonious femes soles violate the ideology of the moral middle-class family which is supposedly protected from the corruption of the public sphere and is reliant on the wife’s dutiful subordination through the marriage contract. In each chapter, I examine the violated relationship between the victim and the felonious feme sole as well as the narrative’s deflection of culpability for heterosexual rape onto the female accomplice(s) within particular legal, commercial, and homosocial contexts, which help to reinforce middle-class ideology of consensual marriage and the moralizing domestic sphere. I suggest the criminalization of femes soles as female accomplices to rape in Daniel Defoe’s Roxana (1724), Samuel Richardson’s Pamela (1740) and Clarissa (1749), and John Cleland’s Fanny Hill (1749) reveals middle-class resistance to women’s legal and economic autonomy in the public sphere as well as the cultural resistance women’s homosocial relationships across class.
Keywords: Domesticity; Eighteenth-century; Female Accomplice; Liberalism; Novel; Rape